ION: design system for the internal systems development sector of the company Brisanet Telecomunicações - Lourenço, Edney Lincoln; Monteiro, Ingrid Teixeira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
A Design System (DS) consists of a set of interconnected standards for building digital products. DS provides a set of elements and components that are repeated across interfaces, such as buttons, text fields, icons, colors, and typography, helping to build a coherent interface. This article describes the construction of the Ion Design System, a product that aims to help designers and front-end developers of the company Brisanet Telecomunicações in the development of user interfaces, through standardization and component documents, as part of the course conclusion work in Digital Design. The process included research with the target audience, analysis of systems and similar products, definition of content, organization of information, testing of interfaces and development of brand, tokens, components and documentation. The Design System was created in the Figma tool, allowing team members to collaborate in the creation and definition of components. The product evaluation highlighted its importance in helping employees build consistent and standardized interfaces. The article presents the results of this work and highlights the relevance of the Ion Design System to improve the interface development experience.